REFLECTIONS ON ANTI-SHARI’AH PRACTICES AMONG MUSLIMS - Balogun, Shittu Abdulazeez (Jurnal Syariah, 2009)
Islam as a way of life guides mankind on how to be true Khalifah (vicegerent) of Allah on earth, by providing all instructions needed to weather the storm of all impediments associated with life on this planet, so as to be successful in this world and the next. As the Shari’ah elucidates criteria for success here and in the hereafter, humankind is always tempted by the Shaytan (Devil) to do the contrary in order to deprive him of the endless bliss of paradise. This paper attempts at unveiling some of the unwholesome activities frowned on by the Shari’ah, which are rampant among Muslims, who are described by Allah (SWT) as the best of mankind. ‘Charity begins at home,’ as a popular saying goes. The reason why the paper focuses on the Muslims alone is that if the set of people expected to be torchbearers are themselves found wanting, what will be the fate of the entire human race? The paper therefore tries to draw attention to some of the activities that may result in punishment by the Almighty, which at the same time militate against effectiveness of da’wah activities, which also revolve around misinterpretation and misapplication of the divine instructions contained in the Shari’ah. Building on information in the literature, the paper also relies on personal experiences and observations of the author in Nigeria. In conclusion, the paper calls on believers to ensure that their actions match their words so as to be good examples for others to emulate, thus portraying Islam in a good image to the outside world.